Screening of wheat (Triticum aestivum L.) genotypes for rust-resistance and assessment on prevalence and distribution of the rust diseases in wheat production fields - Shrestha, Rajan; Mahto, Baidya Nath (Journal of Agriculture and Natural Resources, 2021)
Evaluation of 45 wheat genotypes was performed to quantify genetic responses to inoculation of rust pathogens in aqueous suspension at the early vegetative stage. The study was conducted in field conditions at Plant Pathology Division, Nepal Agricultural Research Council, Lalitpur, Nepal in winter, 2013. Results showed large variations of rust resistance on wheat genotypes. Thirty-six genotypes were susceptible to yellow rust (YR), 18 had high severity, 7 had moderate severity, 6 had low severity, 5 had trace reactions, while 9 were rust-resistant. Old varieties (Lerma-52, Kalayansona, RR-21, NL-30, HD-1982, UP-262, Lumbini, Vinayak, Vaskar, Nepal-297, Nepal-251, BL-1135, Annapurna-4, Achyut, Rohini, and BL-1473) had high severities of YR, but relatively recent cultivars had medium severities. YR was severe (100S) in genotypes HD-1982, Vaskar, Vijay, and Rohini followed by RR-21, NL-30, UP-262, Nepal-297, BL-1135, and Annapurna-4 (90S). The pipeline cultivars: Aditya, NL-971, BL-3503, BL-3623, NL-1008, NL-1064, Becard#1, and Chyakhura-1 had trace to moderate reactions of YR with low severity indices. But varieties Vijay and NL-1055 showed high severity of YR (100S and 80S, respectively). Overall, leaf rust (LR) was minor while stem rust (SR) developed in traces on a single genotype (Annapurna-1). A survey of wheat rusts across 66 production fields revealed the prevalence of YR and LR at high levels, but none on SR. The occurrence of LR was higher than YR; 48.48% vs 36.36% of assessed fields, respectively. YR was a primary concern of rust diseases with most fields under high severity (62.5%) and incidence (54.16%) levels. LR had low incidence and moderate severity levels. A considerable gap exists between an extension of such research outcomes and the producers, who demonstrated little know-how on wheat rusts and varieties. These results may support and enhance varietal selection, breeding programs, and effective management and control strategies against wheat rust diseases.